Carnivorous Walrus and Some Arctic Zoonoses - Fay, Francis H. (ARCTIC, 1960)
Reviews reports of walrus feeding on seal or whale carrion, or killing them for food. Normally, bottom feeders (benthic invertebrates) in shallow, continental waters, walrus eat mammals when/where invertebrates are unobtainable. The (rare) rogue walrus, habitually carnivorous, has a distinctive external appearance. Some catch data are given with estimates of the carnivores, also those with Trichinella infection. The possibility is aired that such animals like the polar bear, have a high vitamin A content in their liver, or may be a source of trichinosis transmissible to man. Comments by T. H. Manning in Arctic, Mar. 1961, p. 76-77.